Downregulated IL-21 Response and T Follicular Helper Cell Exhaustion Correlate with Compromised CD8 T Cell Immunity during Chronic Toxoplasmosis - Moretto, Magali M.; Hwang, SuJin; Khan, Imtiaz A. (Frontiers in Immunology, 2017)
CD8 T cells are important for maintaining the chronicity of Toxoplasma gondii infection. In a T. gondii encephalitis susceptible model, we recently demonstrated that CD4 T cells play an essential helper role in the maintenance of the effector response and CD8 T cell dysfunctionality was linked to CD4 T cell exhaustion. However, CD4 T cells are constituted of different subsets with various functions and the population(s) providing help to the CD8 T cells has not yet been determined. In the present study, Tfh cells (T follicular helper), which are known to be essential for B cell maturation and are one of the main sources of IL-21, were significantly increased during chronic toxoplasmosis. However, at week 7 p.i., when CD8 T cells are exhausted, the Tfh population exhibited increased expression of several inhibitory receptors and levels of IL-21 in the serum were decreased. The importance of IL-21 in the maintenance of CD8 T cells function after T. gondii infection was further demonstrated in IL-21R KO mouse model. Interestingly, while CD8 T cells from both knockout and wild type mice expressed similar levels of PD-1, animals with defective IL-21 signaling exhibited lower polyfunctionality than wild type controls. This reduced polyfunctional ability observed in CD8 T cells from knockout mice was associated with a significant increase in other inhibitory receptors like Tim-3, LAG-3 and 2B4. Furthermore, the animals exhibited greater signs of Toxoplasma reactivation manifested by the reduced number of cysts and increased expression of tachyzoite (replicative form of the parasite) specific genes (SAG1 and ENO2) in the brain. Also, knockout mice displayed a higher frequency of tachyzoite infected monocytes in the blood and spleen. Our findings suggest the importance of Tfh and IL-21 during chronic toxoplasmosis and establish a critical role for this cytokine in regulating CD8 T cell dysfunction by preventing the co-expression of multiple inhibitory receptors during chronic parasitic infection.